‘Millennials and centennials' perspective on streaming narratives in Spain and Mexico: Spiral of silence, bandwagon effect, and third person effect - Fernández-Rodríguez, Carlos; Romero-Rodríguez, Luis M.; Puebla-Martínez, Belén (Research Journal in Advanced Humanities, 2023)
Viewers are increasingly used to the link between entertainment and technology in the current media ecosystem. The success of consuming streaming platforms when watching movies and series shows how the audience is more involved in new forms of viewing, at any time, at any moment, and with any content. This research aimed to examine the perception of millennial and centennial audiences in Spain and Mexico, the two Spanish-speaking countries with the highest streaming consumption, about audiovisual content producers for entertainment. Three theories on public perception (spiral of silence, bandwagon effect, and third-person effect) were used as the basis of the research questions to unravel the extent to which younger audiences in these countries consider that production companies are, or are not, ethical in the representation of what may be labeled as "sensitive topics". The results show that centennials are more confident in their critical perceptions of controversial issues in movies and series, while, on the other hand, millennials approach their perceptions with more cautiousness and confusion.